Exploring the Impact of E-Learning Strategies on Enhancing Workplace English Competence at an Open Distance E-Learning (ODeL) University in South Africa - Maphoto, Kgabo Bridget; Suliman, Zuleika (Research in Social Sciences and Technology- OpenED Network, 2024)
This study explores the implementation of e-learning strategies to enhance workplace English competence. The focus is on a semester module that consists of approximately 10,000 first-year university students in an ODeL context in South Africa. The study’s objective was to collect data and contribute to the field of language learning in the workplace. Guided by the TPACK theory, the investigation employed qualitative research methods, incorporating open-ended evaluation questions and an observation schedule. The instruments allowed for a deep exploration of students’ perspectives and experiences with e-learning strategies, specifically their impact on workplace English competence. The results of the study highlighted the positive effects of e-learning strategies on enhancing workplace English competence. Participants reported improved language skills, increased confidence in communication, and an enhanced ability to meet workplace language requirements. In addition, the findings revealed the significance of interactive multimedia materials, collaborative learning activities, and personalised feedback as effective pedagogical approaches in the module. The contributions of this study lie in its exploration and validation of e-learning strategies for the enhancement of workplace English competence at a distance learning university.